Ovalbumin Hydrolysates Inhibit Nitric Oxide Production in LPS-induced RAW 264.7 Macrophages - Kim, Hyun Suk (Food Sci Anim Resour, 2020)
In this study, ovalbumin (OVA) hydrolysates were prepared using various proteolytic enzymes and the anti-inflammatory activities of the hydrolysates were determined. Also, the potential application of OVA as a functional food material was discussed. The effect of OVA hydrolysates on the inhibition of nitric oxide (NO) production was evaluated via the Griess reaction, and their effects on the expression of inducible NO synthase (inducible nitric oxide synthase, iNOS) were assessed using the quantitative real-time PCR and Western blotting. To determine the mechanism by which OVA hydrolysates activate macrophages, pathways associated with the mitogen-activated protein kinase (MAPK) signaling were evaluated. When the OVA hydrolysates were added to RAW 264.7 cells without lipopolysaccharide (LPS) stimulation, they did not affect the production of NO. However, both the OVA-Protex 6L hydrolysate (OHPT) and OVA-trypsin hydrolysate (OHT) inhibited NO production dose-dependently in LPS- stimulated RAW 264.7 cells. Especially, OHT showed a strong NO-inhibitory activity (62.35% at 2 mg/mL) and suppressed iNOS production and the mRNA expression for iNOS (p<0.05). Also, OHT treatment decreased the phosphorylation levels of Jun amino-terminal kinases (JNK) and extracellular signal-regulated kinases (ERK) in the MAPK signaling pathway. These findings suggested that OVA hydrolysates could be used as an anti-inflammatory agent that prevent the overproduction of NO.